"Glossy green" banks: The disconnect between environmental disclosures and lending activities - Mariassunta Giannetti; Martina Jasova; Maria Loumioti; Caterina Mendicino (European Central Bank (ECB), 2023)
Using confidential information on banks' portfolios, inaccessible to market participants, we show that banks that emphasize the environment in their disclosures extend a higher volume of credit to brown borrowers, without charging higher interest rates or shortening debt maturity. These results cannot be attributed to the financing of borrowers' transition towards greener technologies and are robust to controlling for banks' climate risk discussions. Examining the mechanisms behind the strategic disclosure choices, we highlight that banks are hesitant to sever ties with existing brown borrowers, especially if they exhibit financial underperformance.
Keywords: G11; G15; G21; 330; financial institutions; sustainability reporting; strategic disclosure; credit exposure; zombie lending